Early onset muscle weakness and disruption of muscle proteins in mouse models of spinal muscular atrophy - Justin G. Boyer; Lyndsay M. Murray; Kyle Scott; Yves De Repentigny; Jean‐Marc Renaud; Rashmi Kothary (2013)
The childhood neuromuscular disease spinal muscular atrophy (SMA) is caused by mutations or deletions of the survival motor neuron (SMN1) gene. Although SMA has traditionally been considered a motor neuron disease, the muscle-specific requirement for SMN has never been fully defined. Therefore, the purpose of this study was to investigate muscle defects in mouse models of SMA.We have taken advantage of two different mouse models of SMA, the severe Smn-/-;SMN2 mice and the less severe Smn2B/- mice. We have measured the maximal force produced from control muscles and those of SMA model mice by direct stimulation using an ex vivo apparatus. Immunofluorescence and immunoblot experiments were performed to uncover muscle defects in mouse models of SMA. Means from control and SMA model mice samples were compared using an analysis of variance test and Student's t tests.We report that tibialis anterior (TA) muscles of phenotype stage Smn-/-;SMN2 mice generate 39% less maximal force than muscles from control mice, independently of aberrant motor neuron signal transmission. In addition, during muscle fatigue, the Smn-/-;SMN2 muscle shows early onset and increased unstimulated force compared with controls. Moreover, we demonstrate a significant decrease in force production in muscles from pre-symptomatic Smn-/-;SMN2 and Smn2B/- mice, indicating that muscle weakness is an early event occurring prior to any overt motor neuron loss and muscle denervation. Muscle weakness in mouse models of SMA was associated with a delay in the transition from neonatal to adult isoforms of proteins important for proper muscle contractions, such as ryanodine receptors and sodium channels. Immunoblot analyses of extracts from hindlimb skeletal muscle revealed aberrant levels of the sarcoplasmic reticulum Ca2+ ATPase.The findings from this study reveal a delay in the appearance of mature isoforms of proteins important for muscle contractions, as well as muscle weakness early in the disease etiology, thus highlighting the contributions of skeletal muscle defects to the SMA phenotype.